How Flickr Helps to Know the Place: Visual and Textual Summarization of Geo-location - Takale, SA; Kulkarni, PJ (International Journal of Computer Sciences and Engineering, 2025)
The work proposed here addresses the task of organizing the geo-referenced media on Flickr to generate Visual and Thematic Summarization of specified geo-location. The major challenge addressed in this work is: how to use the unstructured and unrestricted community contributed media and annotations to generate knowledge? The social tags associated with social images suffer from various problems such as, “free nature of tags”, “tag relevance”, and “cold start”. To deal with these problems, we consider ternary interrelations and multiple intra-relations among user, image and tag and model the relations using HOSVD, a Tensor Reduction Technique. As a result, context information for geo-location images is generated using user’s potential annotations. Content and context information for geo-location images and probabilistic generative model is utilized for location visualization. The novel visualization scheme proposed here summarizes the geo-location with a rich display landscape and provides location description using location representative tags. Experiments are performed on geo-tagged Flickr images for various geo-locations. The experimental results have validated the proposed method.